Circulação das discussões teóricas e epistemológicas da comunicação no norte do Brasil - MALCHER, Maria Ataide (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
This paper is guided by the following question: what is the circulation (BRAGA, 2012a) of the discussions from the COMPÓS’ Communication Epistemology Working Group in the training of master degree students in the North, considering the Group as one of the most important environments to update the discussions on this subject in Brazil? Our first focus was to identify the circulation of texts and authors who are members of the Group in the references of dissertations already defended in PPGCOM-UFPA and PPGCCOM-UFAM. We found the citation of some authors from the Group, specially some older texts, which shows a lag of discussions on theories in the North. With this research, we also realize the great presence of other texts about Communication Theories. Therefore, in a second step, we add to the discussion our empirical experiences from classroom in PPGCOM-UFPA, because we find that this still is one of the main environments to circulate such knowledge in the North.